1993
DOI: 10.1172/jci116520
|View full text |Cite
|
Sign up to set email alerts
|

Sucrase-alpha-dextrinase in the rat. Postinsertional conversion to inactive molecular species by a carbohydrate-free diet.

Abstract: Absence of dietary carbohydrate decreases both activities of intestinal brush border sucrase-a-dextrinase. We examined the molecular mechanism causing this decrease. Adult rats were fed chow (70% CHO) or matched carbohydrate-free (CHOfree) diet for 7 d. Sucrase activity decreased by 50% in whole homogenates and brush borders. Enzyme kinetics revealed no change in sucrose affinity (CHO-free K. = 18 mM, chow K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A similar relationship among the specific activities of these enzymes has been reported previously (Thomsen and Tasman-Jones, 1982;Carmona et al, 1996). The sucrase to maltase activity ratio was 0.95; this value is slightly lower than the 1.2 reported by Quan and Gray (1993). Lactase activity was one order of magnitude smaller in comparison with sucrase and maltase.…”
Section: Dietary Fibersupporting
confidence: 87%
See 1 more Smart Citation
“…A similar relationship among the specific activities of these enzymes has been reported previously (Thomsen and Tasman-Jones, 1982;Carmona et al, 1996). The sucrase to maltase activity ratio was 0.95; this value is slightly lower than the 1.2 reported by Quan and Gray (1993). Lactase activity was one order of magnitude smaller in comparison with sucrase and maltase.…”
Section: Dietary Fibersupporting
confidence: 87%
“…Lactase activity was one order of magnitude smaller in comparison with sucrase and maltase. This is due to the fact that the basal diet did not contain lactose to induce higher lactose levels (Quan and Gray, 1993). These results were obtained from experiments in vivo; in vitro experiments were not carried out in these studies.…”
Section: Dietary Fibermentioning
confidence: 99%
“…Sabat and coworkers argued that the increase in activity of these two brush border carbohydrases represents a nonspecific response to the high-protein diet. Conversely, Quan and Gray (1993) found that rats decrease the amount of active sites per enzyme molecule for isomaltase, thereby decreasing their disaccharidase activity in the absence of substrate. Overall, the diverse patterns of maltase and isomaltase activities among the pricklebacks on the high-protein, low-starch diet are not different from those reported for birds and other fishes fed high-versus low-starch diets (Kawai and Ikeda 1972;Buddington and Hilton 1987;Levey et al 1999;Caviedes-Vidal et al 2000), but they expose our uncertainty about the mechanisms underlying why some animals modulate digestive enzyme activities whereas others do not.…”
Section: Discussionmentioning
confidence: 92%
“…14 SI consists of two subunits, sucrase and isomaltase, which are cleaved by luminal proteases but remain associated through noncovalent interactions. 15 The sucrase subunit has both maltase (α-1,4) and sucrase (α-1,2) activities, while the isomaltase subunit has maltase (α-1,4) and isomaltase (α-1,6) activities. 16 SI is therefore involved in the digestion of both sugars and starch.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrase isomaltase (SI) is a highly N - and O -glycosylated brush border type-II membrane protein with various α-glucosidase activities and is trafficked to the cell surface through association with lipid rafts . SI consists of two subunits, sucrase and isomaltase, which are cleaved by luminal proteases but remain associated through noncovalent interactions . The sucrase subunit has both maltase (α-1,4) and sucrase (α-1,2) activities, while the isomaltase subunit has maltase (α-1,4) and isomaltase (α-1,6) activities .…”
Section: Introductionmentioning
confidence: 99%